Systematic Literature Review of Using Narrative Interventions to Support Character Development in Children with Trauma - Nurin Wahida Amalin, Aslizam; Athirah, Azhar (Springer, Singapore, 2026)
This systematic literature review (SLR) aims to explore the potential of narratives as a mechanism to support character development in children, particularly those affected by trauma. This research is organized around three objectives: the role of storytellers or narrators; the effects of storytelling on traumatized children; and barriers to implementing storytelling. The methodology involves a detailed protocol for literature selection, including criteria for inclusion and exclusion, ensuring a focused and relevant review. By employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, this study will systematically search and analyze literature from SCOPUS and Web of Science (WoS) to address pivotal questions regarding the important questions of narrative interventions. Key expected outcomes include identifying the effect of narratives and understanding the role of storytellers in therapeutic and educational settings to support the character development of traumatized children. By integrating findings from multiple disciplines and contexts, this review hopes to contribute to a nuanced understanding of how narrative interventions can be applied to their development. The conclusion from this SLR shows that narrative intervention is an important and effective tool for enhancing character development in traumatized children, offering practical insights for educators and therapists on how narratives can foster resilience and emotional growth in children.